2020
DOI: 10.2319/080619-517.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rapid maxillary expansion on temporomandibular joints:

Abstract: Objective To evaluate the impact of rapid maxillary expansion (RME) on the condylar position, disc joint, joint space, and interarticular relationship in growing patients. Materials and Methods A systematic search was performed in nine databases. The clinical studies selected included those with pre- and post-magnetic resonance, conventional computed tomography or cone beam tomography in growing patients. Risk of bias assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The tool consists of 12 to 14 items assessing sources of bias such as patient selection, study power, and confounding ( NHLBI, 2014 ). NHLBI has been widely used in previous literature reviews ( Akpan et al, 2020 ; Gupta et al., 2017 ; Haighton et al, 2019 ; Ismaiel et al, 2021 ; Pires, 2022 ; Torres et al, 2020 ). Inter-rater reliability was conducted for the agreement between raters for each question of the assessment tools.…”
Section: Methodsmentioning
confidence: 99%
“…The tool consists of 12 to 14 items assessing sources of bias such as patient selection, study power, and confounding ( NHLBI, 2014 ). NHLBI has been widely used in previous literature reviews ( Akpan et al, 2020 ; Gupta et al., 2017 ; Haighton et al, 2019 ; Ismaiel et al, 2021 ; Pires, 2022 ; Torres et al, 2020 ). Inter-rater reliability was conducted for the agreement between raters for each question of the assessment tools.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have focused on evaluating the dentoalveolar effects of MARPE, however, the condylar response to this procedure is not well understood, especially in patients with MD. It has been clinically reported that early intervention can promote condylar growth, correct mandibular deviation, achieving symmetrical growth of jaw bones [10][11][12]. However, the adaptive changes of the condyle in adults with Class III malocclusion and horizontal MD after expansion treatment remain to be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the growth of the condyle increases in patients with Class II malocclusions after treatment with functional appliances such as the activator, Twin-block and Herbst [10,13,14]. For patients with growth and development, Arat et al [11] and Torres et al [12] observed that rapid maxillary expansion (RME) induced bone modeling in the condyle. Furthermore, based on handwrist radiography, the Herbst appliance has been shown to promote remodeling at the posterosuperior border in patients with minimal or no residual growth [15], and skeletal facial growth potential remained even after the age of 20 [16].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review 4 evaluating conventional rapid maxillary expansion in growing patients showed that there is no change in the position and shape of the articular disc immediately after expansion. However, there is no evidence available on the subject when using, in adults, the rapid expansion of the surgically assisted maxilla.…”
Section: Introductionmentioning
confidence: 99%